Tangier disease may cause early onset of atherosclerotic cerebral infarction: A case report. Issue 39 (September 2018) - Liang, Zhigang; Li, Wei; Yang, Shaowan; Liu, Zhuli; Sun, Xuwen; Gao, Xiaoyu; Yu, Guoping
Abstract: Rationale: The present study explored the relationship between the adenosine triphosphate (ATP)-binding cassette A1 ( ABCA1 ) gene, atherosclerosis, and cerebral infarction. The diagnosis and treatment ideas of stroke caused by Tangier disease via the summary of the diagnosis and treatment process of one case with juvenile stroke were explored. The relevant literature on the clinical manifestations, laboratory examinations, and treatment of Tangier disease was reviewed. Patient concerns: The brain magnetic resonance imaging (MRI) of a juvenile man with acute onset of sudden right limb weakness and speechlessness revealed infarct lesions. The laboratory tests found low serum high-density lipoprotein (HDL), while further genetic testing identified ABCD1 gene mutation. The mother also carried the mutant gene. Diagnoses: Tangier disease was diagnosed. Interventions: Statin treatment was administered for platelet aggregation. Outcomes: After 3 years of follow-up, the patient was declared to be in a stable condition. Lessons: ABCA1 gene mutation caused early onset of atherosclerosis, leading to the occurrence of cerebral infarction. The cerebral infarction associated with reduced high-density lipoprotein (HDL), was under intensive focus with respect to ABCA1 gene. Child and Juvenile stroke patients with low HDL should not be excluded from the possibility of Tangier disease.